(untitled) (Pharmacy Practice, 2009)
Pharmaceutical advertisement of drugs is a means of advocating drug use and their selling but not a substitute for drug formulary to guide physicians in safe prescribing. Objectives: To evaluate drug advertisements in Nigerian and other African medical journals for their adequacy of pharmacological information. Methods: Twenty four issues from each of West African Journal of Medicine (WAJM), East African Medical Journal (EAMJ), South African Medical Journal (SAMJ), Nigerian Medical Practitioner (NMP), Nigerian Quarterly Journal of Hospital Medicine (NQJHM) and Nigerian Postgraduate Medical Journal (NPMJ) were reviewed. While EAMJ, SAMJ and NMP are published monthly, the WAJM, NQJHM and NPMJ are published quarterly. The monthly journals were reviewed between January 2005 and December 2006, and the quarterly journals between January 2001 and December 2006. The drug information with regards to brand/non-proprietary name, pharmacological data, clinical information, pharmaceutical information and legal aspects was evaluated as per World Health Organisation (WHO) criteria. Counts in all categories were collated for each advertiser. Results: Forty one pharmaceutical companies made 192 advertisements. 112 (58.3%) of these advertisements were made in the African medical journals. Pfizer (20.3%) and Swipha (12.5%) topped the list of the advertising companies. Four (2.1%) adverts mentioned generic names only, 157 (81.8%) mentioned clinical indications. Adults and children dosage (39.6%), use in special situations such as pregnancy and renal or liver problems (36.5%), adverse effects (30.2%), average duration of treatment (26.0%), and potential for interaction with other drugs (18.7%) were less discussed. Pharmaceutical information such as available dosage forms and product and package information summary of the generic and proprietary names, the formulation strength, active ingredient, route of administration, batch number, manufactured and expiry dates, and the manufacturer on both the container and pack of the drug were mentioned in 65.6% and 50% adverts, respectively. The product and package descriptions were provided in 57 (72.2%) Nigerian medical journals, which was significantly higher than in other African medical journals 39 (37.9%) (P<0.001). Conclusions: None of the drug advertisements in the journals adequately provided the basic information required by the WHO for appropriate prescribing. More guidance and regulation is needed to ensure adequate information is provided.